Tuning the basicity of ionic liquids for efficient synthesis of alkylidene carbonates from CO2 at atmospheric pressure. Issue 50 (31st May 2016) - Chen, Kaihong; Shi, Guiling; Dao, Rina; Mei, Ke; Zhou, Xiuyuan; Li, Haoran; Wang, Congmin
Abstract : A method for the efficient synthesis of alkylidene carbonates from CO2 by tuning the basicity of ionic liquids was reported. Abstract : A strategy to achieve the efficient synthesis of alkylidene carbonates from CO2 at atmospheric pressure by tuning the basicity of ionic liquids was developed. Excellent yields were obtained due to basic ionic liquids' dual roles both as absorbents and as activators. The reaction mechanism was investigated through a combination of NMR spectroscopy, controlled experiments and quantum calculations, indicating the importance of a moderate basicity.